THE EFFECT OF THE IMPLEMENTATION OF DOROTHEA OREM'S SELF-CARE THEORY ON THE INDEPENDENCE OF ELEMENTARY SCHOOL CHILDREN IN MAINTAINING PERSONAL HYGIENE - Ririnisahawaitun Ririnisahawaitun; Hikmah Lia Basuni; Ahyar Rosidi; Suhaemi Suhaemi (Jurnal Keperawatan Sriwijaya, 2026)
Aim: Children's independence in maintaining personal hygiene is an important part of the formation of healthy living behaviors from an early age. The aim of this study is to determine the influence of the implementation of Dorothea Orem's Self Care Theory on children's independence in maintaining personal hygiene at SDN 03 Dasan Dobol Lenek Baru Method:This study is a quasi-experimental quantitative design with a pretest-posttest control group design approach. The sampling technique used was stratified random sampling with a sample of 100 students in grades III-VI. The experimental group consisted of 50 students who were given an intervention using an educational video, while the control group consisted of 50 students who were given an educational leaflet. Data collection was conducted using a Likert scale questionnaire. Data analysis used the Wilcoxon test and the Independent Sample T-Test. Result: Children's independence significantly improved before and after the intervention in both the experimental and control groups (p value= 0.000). The results of the Independent Sample T-Test showed significant differences between the two groups after the intervention (p value= 0.037) Conclusion: Implementing Dorothea Orem's Self-Care Theory significantly increases children's independence in maintaining personal hygiene. Video media is more effective than leaflets in delivering personal hygiene education to elementary school-age children